Abundance of Diadema antillarum (Echinodermata: Echinoidea) in the coasts of Venezuela - Noriega, Nicida (2006)
Diadema antillarum is a shallow-water sea-urchin from the tropical Atlantic whose populations almost disappeared in 1983-84 because of widespread mortalities which reached 87-100 %. In Venezuela, urchin population densities before the mortality event were comparable to those of other Caribbean regions; however, later abundancies remain unknown. The objectives of this study were to evaluate the recent densities of certain D. antillarum populations along the Venezuelan coasts and compare the densities at the Parque Nacional Mochima before and after the mortality. At each location urchin densities were determined by means of transects using 1m2 quadrats as sampling units. The highest mean densities were observed at the sites on the central coast: Ensenada de Oricao, 0.28 ind/m2 (2002) and 1.05 ind/m2 (2003), and Chichiriviche de la Costa, 0.84 ind/m2 (2002) and 0.74 ind/m2 (2003). In Mochima, the mean density before the mortality for D. antillarum oscillated between 0.28 and 4 ind/m2, after the mortality event the mean density varied between 0.15 ind/m2 (2000) and 0.47 ind/m2 (2000). The populations of D. antillarum studied at Parque Nacional Morrocoy and Refugio de Fauna Silvestre Cuare showed highest densities at Playuela (0.43 ind/m2) and Cayo Sur (0.95 ind/m2) respectively, whereas other sites showed densities below 0.1 ind/m2. The density registered at Playuela in 2003 is lower than that reported before the mortality event (0.58-3.64 ind/m2). The density for Parque Nacional Archipiélago de Los Roques,specifically for the Arrecife de Herradura remained constant between 2002 and 2003 with values between 0.22- 0.23 ind/m2 respectively. To conclude, the sea urchin abundancies observed at most of the Venezuelan coastal sites that we studied were higher than those reported for other areas of the northern Caribbean, even though the values have not yet returned to those preceding the 1984 mass-mortality event, due to the slow recovery of the populations.